Using Generative AI Midjourney to enhance divergent and convergent thinking in an architect's creative design process - Tan, Linus; Luhrs, Max (The Design journal, 2024)
Architects use a range of tools, from the traditional pencil to Virtual Reality technologies to prototype and articulate their creative designs. In recent years, Generative Artificial Intelligence (GenAI) software has reached the mainstream and there is an exponential appearance of GenAI images that portray architectural designs. This article documents an architectural design methodology that uses Midjourney, a text-to-image GenAI software, as a design tool that enhances architects' creativity. Prompted by a design brief, we used Midjourney to accelerate (1) the identification and refinement process of developing a prospective user and (2) the ideation process of creating different desirable spaces for the designed user.